PEMETAAN POTENSI BENCANA ALAM (GEO-DISASTER) AKIBAT PENAMBANGAN BIJIH TIMAH DI KECAMATAN JEBUS DAN PARIT TIGA, KABUPATEN BANGKA BARAT - Irvani Irvani; Taman Tono (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2014)
The study area is a tin mining region in hundred years, located in Jebus and Parit Tiga District, West Bangka Regency, Bangka Belitung Archipelago Province. Identifying some geo-disaster potential, in order that the geo-disaster mapping caused by tin mining activity is done. The research is done by observing geological, geomorphological, erosion dan sedimentation conditions, mass movement, abrasion, dan floods. Geo-disaster potential is ilustratrated in map as result of work using geographic information system (GIS) software. Geodisasters that come from tin mining at study area are erosion, sedimentation, mass movement, floods and abrasion on the beach, which is about 67% area.